Persistence of a Core Microbiome Through the Ontogeny of a Multi-Host Parasite - Jorge, Fátima; Dheilly, Nolwenn M.; Poulin, Robert (Frontiers in Microbiology, 2020)
Animal microbiomes influence their development, behaviour and interactions with other organisms. Parasitic metazoans also harbour microbial communities; although they are likely to modulate host-parasite interactions, little is known about parasite microbiomes. The persistence of microbial communities throughout the life of a parasite is particularly challenging for helminths with complex life cycles. These parasites undergo major morphological changes during their life, and parasitise host species that are immunologically, physiologically, and phylogenetically very different. Here, using 16S amplicon sequencing, we characterise the microbiome of the trematode Coitocaecum parvum across four of its life stages: sporocysts, metacercariae and adults inhabiting (respectively) snails, crustaceans and fish, as well as free-living cercariae. Our results demonstrate that, at each life stage, the parasite possesses a phylogenetically diverse microbiome, distinct from that of its hosts or the external environment. The parasite’s microbiome comprises bacterial taxa specific to each life stage in different hosts, as well as a small core that persists across the parasite’s whole life. The existence of an ontogenetically and vertically transmitted core microbiome is supported by the findings that the diversity and taxonomic composition of the microbiome does not vary significantly among life stages, and that the main source of microbial taxa at any life stage is the previous life stage. Our results suggest that microbes are an integrated component of the trematode, possibly shaping its phenotype and host-parasite interactions.